The making of South East Asia - Coedès, G. (Univ. of California, 1967)
Contents: The pattern of settlement in Indochina; The founding of the first Indochinese states; The Indochises states from the sixth to the thirteenth century; The crisis of the thirteenth century and the decline of Indian cultural influence; The Indochinese states after the thirteenth century.